The relationship between leadership style, emotional intelligence and organisational learning among academic staff in Malaysian higher educational institutions / Hanisah Bon (Kasbon) - Bon (Kasbon), Hanisah (2012)
This study was conducted to investigate the relationship between perceived leadership styles and emotional intelligence on organisational learning among academics of Malaysian higher educational institutions. Specifically, the study attempted to 1) investigate the level of organisational learning, emotional intelligence and perceived leadership styles of academics of higher education institutions of Malaysia; 2) identify the relationship of perceived leadership styles and emotional intelligence on organisational learning of academics of higher education institutions of Malaysia and 3) identify the contributor of each significant of leadership styles and emotional intelligence on the variance of organisational learning.The questionnaire was distributed to a total of 150 randomly selected respondents and the responses rate was 83% or 125 questionnaires were returned and only 120 questionnaires were duly completed and used in analysis. Data were collected using the survey method and were descriptive statistically analysed. From the study, the findings revealed that the level of organisational learning perceived by the respondents was at moderate level and perceived transformational and transactional styles were both at moderate but slightly higher for transformational. In addition, most academics scored high for their emotional intelligence level. For the relationship between organisational learning and the independent variables, the findings suggested that there was a positive and moderate relationship between organisational learning and transformational leadership and also moderate relationship with one of the emotional intelligence cluster namely self emotional appraisal. In terms of determining the contributor of each significant of leadership styles and emotional intelligence on the variance of organisational learning, it revealed that 35.5% of the variance in organisational learning scores can be predicted from the variables of transformational leadership and self emotional appraisal. From the findings of the study, it could be summarised that transformational leadership plays a significant role in organisational learning process as a whole. In addition, learning environment in organisations could facilitate organisational members to enhance emotional intelligence ability and at the same time, promote continuous learning both at individual and organisational level.